Effect of 3 months vitamin E supplementation on indices of the cellular and humoral immune response in elderly subjects - De Waart, Frouwkje G.; Portengen, Lützen; Doekes, Gert; Verwaal, Corné J.; Kok, Frans J. (British journal of nutrition, 1997)
It has been suggested that decreased immune responsiveness in the elderly may be counteracted by the antioxidant vitamin E. In a 3-month double-blind placebo-controlled intervention trial among elderly subjects aged 65 years and over we studied the effects of a daily dose of 100 mg dl-α-tocopheryl acetate on the cellular immune responsiveness (n 52) measured by the in vitro response of peripheral blood mononuclear cells (PBMC) to the mitogens concanavalin A (ConA) and phytohaemagglutinin (PHA). Also effects on the humoral immune responsiveness (n 74) were investigated by measuring immunoglobulin (Ig)G, IgG4 and IgA antibody concentrations against various common antigens. In the vitamin E group plasma α-tocopherol increased by 51 % (P = 0.0001) during intervention whereas no significant changes were observed in the control group. Initial proliferative PBMC responses differed between the vitamin E group and the control group whereas all other baseline characteristics were comparable. No significant changes were observed in cellular immune responsiveness when adjusted for initial values in either the control group or the vitamin E group and, after the trial period, responses in the two groups were not significantly different. Similarly, in the vitamin E group no significant changes were found in levels of IgG and IgA raised against Penicillium or IgG4 raised against egg, milk, or wheat proteins. In the control group small but significant increases in IgG anti-Penicillium (P <0.05) and decreases in IgG4 against milk proteins (P < 0.05) were observed. Thus, the results of this study performed with the relatively low dose of 100 mg dl-α-tocopheryl acetate do not support the claims of a beneficial effect of vitamin E intake on the overall immune responsiveness of elderly subjects.